(untitled) (Political Science Journal, 2025)
Indeed, national fertility levels reach nearly replacement level in Nepal, yet sizable disparities are observed at the district level in terms of fertility. While some districts exhibit fertility below replacement levels, others have high fertility levels, which are mainly recognized to age. This study endeavors by examining age-specific fertility rates (ASFRs) and total fertility rates (TFRs) at the district level to search the extremes in fertility and its geographic as well as demographic dimensions of fertility transitions in Nepal. The study used an analytical method using fertility data from the 2021 National Population and Housing Census (NPHC), direct as well as indirect methods of estimations were used. Age-specific fertility rates were computed using births that occurred in the past 12 months before the census. The indirect estimates were generated using the Arriaga method that relied on average children ever born (CEB) from the 2011 and 2021 censuses. The total number of districts analyzed included 77, concentrating on the highest and the lowest fertility. Descriptive statistics, fertility equations and comparison of ASFRs and TFRs between districts were then utilized for analysis. The high fertility districts such as Rautahat (TFR 4.33), Dhanusa (3.94), and Achham (3.47) could get born each child aged even from their uneasy older cohorts; in contrast, Lalitpur (TFR 1.24), Kathmandu (1.29), Bhaktapur (1.31) displays late fertility beginning and rather less children after age 35. The differences in fertility in Nepal are, however, caused by long-standing social problems, which are really geographical and service-related inequalities needing targeted interventions at a district level. Policies should therefore promote adolescent reproductive health, delay early marriage, and strengthen localized family planning programs that are personalized for proffering district-specific fertility profiles.